2014
DOI: 10.5742/mejpa.2014.92525
|View full text |Cite
|
Sign up to set email alerts
|

Health - Related Quality of Life in Transfusion - Dependent Thalassemia Major Patients and Associated Factors in Dubai , UAE , 2011

Abstract: Background: Exploring knowledge about and associated factors of health-related quality of life (HRQOL) among patients with thalassemia is essential in developing more suitable clinical, counseling, and social support programs to improve treatment outcomes of these patients. Objectives: To investigate knowledge about HRQOL in transfusion-dependent thalassemia major patients, and to identify the socio-demographic and disease related factors that affect their quality of life (QOL). Methods: A cross-sectional stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…(Table 3). In an experimental study of (86) school age Iranian children with thalassemia major it was found that the thalassemia major had a strong negative impact on emotional aspect of children more than social, and school achievement aspect (14) .Additional support was found study of (269) UAE children;It was conducted to assess the physical and psychosocial health of thalassemia children.The study result indicated that there were the most affected dimensions with emotional being affected more than any dimension by social, physical, and school achievement (15) . The results of the present study revealed that there were no significant differences between children response and information of their parents regarding the overall children psychosocial aspect of thalassemia, these findings revealed that majority of thalassemic children had always suffered problem of overall psychosocial status.…”
Section: Discussionmentioning
confidence: 90%
“…(Table 3). In an experimental study of (86) school age Iranian children with thalassemia major it was found that the thalassemia major had a strong negative impact on emotional aspect of children more than social, and school achievement aspect (14) .Additional support was found study of (269) UAE children;It was conducted to assess the physical and psychosocial health of thalassemia children.The study result indicated that there were the most affected dimensions with emotional being affected more than any dimension by social, physical, and school achievement (15) . The results of the present study revealed that there were no significant differences between children response and information of their parents regarding the overall children psychosocial aspect of thalassemia, these findings revealed that majority of thalassemic children had always suffered problem of overall psychosocial status.…”
Section: Discussionmentioning
confidence: 90%